2017
DOI: 10.1108/jmp-07-2016-0220
|View full text |Cite
|
Sign up to set email alerts
|

Personality perception based on LinkedIn profiles

Abstract: Purpose-Job-related social networking websites (e.g. LinkedIn) are often used in the recruitment process because the profiles contain valuable information such as education level and work experience. The purpose of this paper is to investigate whether people can accurately infer a profile owner's self-rated personality traits based on the profile on a job-related social networking site. Design/methodology/approach-In two studies, raters inferred personality traits (the Big Five and self-presentation) from Link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
6

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 47 publications
(74 reference statements)
2
34
0
6
Order By: Relevance
“…Similarly, Jusupova et al [23] used demographic and social activity information to predict personality of Portuguese users, whereas Liu et al [24] proposed a deep-learning-based approach to build hierarchical word and sentence representations that is able to infer personality of users from three languages: English, Italian, and Spanish. Van de Ven et al [25] based their analyses on LinkedIn, a job-related social media platform, yet they did not find strong correlations between personality traits and user profiles, except for Extraversion. YouYou et al [26] demonstrated that computer-based judgments about an individual can be more accurate than those made by friends, spouse, and even the individual himself, if sufficient data is available.…”
Section: Related Workmentioning
confidence: 99%
“…Similarly, Jusupova et al [23] used demographic and social activity information to predict personality of Portuguese users, whereas Liu et al [24] proposed a deep-learning-based approach to build hierarchical word and sentence representations that is able to infer personality of users from three languages: English, Italian, and Spanish. Van de Ven et al [25] based their analyses on LinkedIn, a job-related social media platform, yet they did not find strong correlations between personality traits and user profiles, except for Extraversion. YouYou et al [26] demonstrated that computer-based judgments about an individual can be more accurate than those made by friends, spouse, and even the individual himself, if sufficient data is available.…”
Section: Related Workmentioning
confidence: 99%
“…It can be used: 1) to attract jobseekers through employer branding; 2) to announce job vacancies on the employer's Facebook or LinkedIn site; 3) to enable employees to share information about job vacancies on their own sites; 4) to search for and make contact with potential employees; and 5) to search for information about candidates as part of the screening process (e.g. Hedenus & Backman, 2018;McDonald et al, 2016;Melanthiou, Pavlou, & Constantinou, 2015;Roth, Bobko, Van Iddekinge, & Thatcher, 2016;van de Ven, Bogaert, Serlie, Brandt & Denissen, 2017). Even though the use of informal contacts still constitutes the most common recruitment strategy, surveys conducted by the Swedish Chamber of Commerce (2017) show that the use of internet and social media in recruitment seems to be increasing.…”
Section: Previous Research and Theorymentioning
confidence: 99%
“…Could researchers make defensible inferences about employment outcomes collected from social media? Although there has yet to be a published empirical investigation on this topic, previous research has examined the dependability of other types of data collected online (Gosling, Vazire, Srivastava, & John, 2004;van de Ven, Bogaert, Serlie, Brandt, & Denissen, 2017). For example, Casler, Bickel, and Hackett (2013) compared experimental data collected from participants recruited through three different means: social media websites, Amazon's MTurk, and word of mouth.…”
Section: Research Questionsmentioning
confidence: 99%